Racial equity on college campuses : connecting research and practice - Johnson, Royel M.; Anya, Uju; Garces, Liliana M. (State University of New York Press, 2022)
"Offers insight into race-based disparities in higher education and practical tools for advancing racial equity on college and university campuses"-- Provided by publisher.
Keywords: Racial justice in education -- United States.; Discrimination in higher education -- United States.; Educational equalization -- United States.; Minorities -- Education (Higher) -- United States.; Minority college students -- United States.; Discrimination dans l'enseignement supérieur -- États-Unis.; Démocratisation de l'enseignement -- États-Unis.; Minorités -- Enseignement supérieur -- États-Unis.; Étudiants issus des minorités -- États-Unis.; EDUCATION / Higher.; Discrimination in higher education; Educational equalization; Minorities -- Education (Higher); Minority college students; Racial justice in education; United States; Essays.